Evaluating Zinc Nutrition In Perennial Ryegrass Grown In An Andisol - Jason W. Stuckey; José Verdejo; Sebastián García; Dante Pinochet; Carolina Yáñez; Yu. A. Krutyakov; Alexander Neaman (Geography, Environment, Sustainability)
Zinc is an essential nutrient for humans, animals, and plants. Zinc uptake by crops is dictated by zinc availability in the soil, which in turn may be dictated, at least in part, by soil mineralogy. Little is known about the phytoavailability of Zn in Andisols, which are important agricultural soils in volcanic regions, such as Japan, New Zealand, and southern Chile. In this study, we assessed the vegetative growth response of perennial ryegrass (Lolium perenne, L.) to Zn fertilization in an Andisol from southern Chile. Ryegrass was grown in a greenhouse pot experiment with twelve rates of Zn application from 0 to 6075 mg Zn/kg soil. After 63 days, shoot length, specific leaf area, and biomass were measured. Foliar Zn concentrations were measured and correlated with plant-available Zn as measured by a diethylenetriaminepentaacetic acid (DTPA)-soil extraction (DTPA-Zn hereafter). Zinc toxicity to ryegrass was assessed using the Toxicity Relationship Analysis Program. This study demonstrated that a DTPA-Zn level of 1 mg Zn/kg soil was not limiting for ryegrass growth. Although Zn fertilization did not improve ryegrass growth in the studied Andisol, this study still has practical implications. Zinc deficiency in humans is a global problem and increasing Zn in staple food and forage crops may require Zn fertilization. This study suggests that Andisols can be fertilized with high doses of Zn without a risk of causing Zn toxicity to crops. However, a DTPA-Zn level of >489 mg Zn/kg soil decreased shoot length, indicating a toxicity response.